KONFLIK SOSIAL DALAM NOVEL MY SECRET DAYS KARYA YUANITA WONG (KAJIAN RESEPSI SASTRA) - Aditami, Novie Surya (Jurnal Sastra Aksara, 2018)
Writing literary works, especially novel, there must be things that aimed to attract readers. One of them was the conflict in the presented story. The conflicts could be internal conflicts or social conflicts. Social conflict was a conflict that occurs between two or more parties in the community and tried to overthrow one another. This research aimed to describe the readers' responses to the causes of the emergence of social conflict and the attitudes of the main characters toward the social conflict in Yuanita Wong's My Secret Days novel. This research used descriptive qualitative research methods and used a literature reception approach and questionnaire techniques. Literary reception is defined as readers’acceptance. This research used adolescents in Banyuajuh Village as the objects of research. The results showed: the readers' response to the causes of the emergence of social conflict and the attitude of the main character in the social conflict in the novel My Secret Days by Yuanita Wong was very diverse. In terms of language and opinion delivery by respondents, some answered in detail, briefly, and even deviated from the contents contained in the novel.